2013
DOI: 10.1002/ece3.711
|View full text |Cite
|
Sign up to set email alerts
|

Distinct subspecies or phenotypic plasticity? Genetic and morphological differentiation of mountain honey bees in East Africa

Abstract: Identifying the forces shaping intraspecific phenotypic and genotypic divergence are of key importance in evolutionary biology. Phenotypic divergence may result from local adaptation or, especially in species with strong gene flow, from pronounced phenotypic plasticity. Here, we examine morphological and genetic divergence among populations of the western honey bee Apis mellifera in the topographically heterogeneous East African region. The currently accepted “mountain refugia hypothesis” states that populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 73 publications
4
36
0
1
Order By: Relevance
“…The present study demonstrated that, due to intense gene flow among the studied colonies, the high variability in wing size and the pronounced differences between apiaries and ecoregions are the result of phenotypic plasticity rather than genetic divergence among populations. This confirms the results reported by Gruber et al (2013). In the present study, therefore, we were able to characterize the differences between honey bee populations using multivariate analysis in combination with wing-venation morphometric data.…”
Section: Discussionsupporting
confidence: 92%
“…The present study demonstrated that, due to intense gene flow among the studied colonies, the high variability in wing size and the pronounced differences between apiaries and ecoregions are the result of phenotypic plasticity rather than genetic divergence among populations. This confirms the results reported by Gruber et al (2013). In the present study, therefore, we were able to characterize the differences between honey bee populations using multivariate analysis in combination with wing-venation morphometric data.…”
Section: Discussionsupporting
confidence: 92%
“…Genetic diversity plays an important role in the adaptation capabilities of species and their susceptibility to environmental changes (Raymond et al ., ). Measurements of the relationship between genetic variation and adaptive traits have already been conducted in a number of species, which showed that species with high level of genetic diversity and gene flow have higher phenotypic plasticity (Reed & Frankham, ; Ghalambor et al ., ; Gruber et al ., ). For example, LU8 with lower genetic variation had a weaker adaptability than other populations in the Loess Plateau, and other populations with higher genetic variation had a stronger adaptability to establish in a new environment (Yan et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…2011; Gruber et al 2013). In recent years, the use of single-nucleotiode polymorphisms has also become important (Whitfield et al 2006).…”
Section: Introductionmentioning
confidence: 99%